Ash Carbonation Using Carbon Dioxide Captured By Carbonates - Aminuddin, Aizat Mohd (Universiti Sains Malaysia, 2017)
Rise of environmental pollutants such as carbon dioxide (CO2) and oil palm waste have been a grave concern in Malaysia. In an effort to reduce the pollutants, carbonation of palm oil fuel ash (POFA) using CO2 locked in potassium hydrogen carbonates (KHCO3) was investigated at different operating conditions and setup. Raw POFA was first prepared by drying, grinding and calcining. After preparation, the ash was subsequently carbonated with KHCO3 in aqueous condition using water bath shaker. The effect of calcination (500-800 °C at 90 & 180 min), reaction time (2-30 min), reaction temperature (30-75 °C) and stirring rate (100-250 rpm) were also evaluated. The best conditions obtained using complexometric titration of Ca2+ were at 800 °C (180 min) calcination, 75 °C (20 min) reaction as well as 250 rpm which have resulted in 0.0023, 0.0079 and 0.0043 g CO2 captured/g POFA used respectively. Using similar operating conditions (60 °C), the carbonation reaction was repeated and compared using incubator shaker and microwave synthesizer with different heat dissipation. Microwave synthesizer demonstrates the best equipment to be used for carbonation, with CO2 capture of 0.0067 g/g POFA. At 75 °C, POFA was able to capture 0.0098 g CO2/g POFA. The reaction time was then varied for the microwave synthesizer which shows the constant performance starting from the 10th min. The POFA were characterized using scanning electron microscope (SEM) that shows a reduced carbon and impurities present in the ash after calcination.